PENGUKURAN MOTIVASI KERJA PANITIA PENGADAAN BARANG ATAU JASA PEMERINTAH (Studi Kasus Dinas Pendidikan Provinsi Jawa Tengah) - Darminto Pujotomo; Zainal Fanani R; Prasetyo Dwi Utomo (Diponegoro University, 2010)
Improvment Job Motivation need to organization for better job. Aims this reserach is redesign job ofprocurement comitte in Dinas Pendidikan Propinsi Jawa Tengah for improving job motivation. This reserachbased on job characteristic, such various skills, job identification, job significant, otonomy, and feedback. Themethod Job Doiagnostic Survey (JDS) from Hackman and Oldham, used for queaionaire design in comitteprocurerment responden.